Strategi Social Media Marketing Restoran Tanpa Sertifikat Halal Dalam Membangun Kepercayaan Konsumen Melalui Instagram - Chininta Rizka Angelia; Juliadi, Rismi; Masri Gasa, Frederik (Jurnal Public Relations (J-PR), 2025)
The halalness of food and beverage products is a major concern for most consumers in Indonesia. Restaurants with halal certificates tend to be more in demand by Muslim and non-Muslim consumers, because their cleanliness and halalness are guaranteed. Restaurants without halal certificates use social media as a marketing tool to overcome the obstacles of halal status and increase their competitiveness. This study aims to analyze the marketing strategy of restaurants without halal certificates builds consumer trust through Instagram. This study uses the concept of Social Media Marketing, a qualitative approach and a case study method. Data collection was conducted through in-depth interviews with the BOGA Group Managers. The results of the study show that even though it does not have a halal certificate, the restaurant implements information transparency, attractive visual content, and active interaction with consumers on Instagram. The main message to be conveyed is "Leten is The Best Paradise Dynasty with no pork no lard". The contents uploaded to the page @leten.byparadisedynasty are also strengthened by the use of ads, KOL, and foodies, to create traffic on Instagram. Leten is able to overcome the challenges of halal issues without sacrificing public trust.